2021
DOI: 10.3892/mmr.2021.12372
|View full text |Cite
|
Sign up to set email alerts
|

Theories behind the effect of starch‑ and sucrose‑reduced diets on gastrointestinal symptoms in irritable bowel syndrome (Review)

Abstract: increased amounts of starch and sugar have been added to the diet in the Western world during the last decades. undigested carbohydrates lead to bacterial fermentation and gas production with diffusion of water, causing abdominal bloating, pain and diarrhea. Therefore, dietary advice is the first line of treatment of irritable bowel syndrome (IBS), a disease characterized by abdominal pain and altered bowel habits without any organic findings. recently, a diet with a reduction of starch and sucrose led to a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…The aim of the study, molecular analysis of SLC2A5 gene concerning gene variants associated with fructose malabsorption, was based on other studies showing the role of SNPs/mutations affecting the uptake/metabolism of related sugars. Variants including partial deficiency of sucrose-isomaltase were shown to be associated with IBS [ 35 ]. Analysis of UK biobank data revealed that gene variants in human ketohexokinase gene are associated with loss of function and resulting in the rare benign condition of fructosuria [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the study, molecular analysis of SLC2A5 gene concerning gene variants associated with fructose malabsorption, was based on other studies showing the role of SNPs/mutations affecting the uptake/metabolism of related sugars. Variants including partial deficiency of sucrose-isomaltase were shown to be associated with IBS [ 35 ]. Analysis of UK biobank data revealed that gene variants in human ketohexokinase gene are associated with loss of function and resulting in the rare benign condition of fructosuria [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the study, molecular analysis of SLC2A5/GLUT5 gene concerning gene variants associated to fructose malabsorption, was based on other studies showing the role of SNPs/mutations affecting the uptake/metabolism of related sugars. Variants including partial de ciency of sucrose-isomaltase were shown to be associated with IBS (35). Analysis of UK biobank data revealed that gene variants in human ketohexokinase gene are associated with loss of function and resulting in the rare benign condition of fructosuria (36).…”
Section: Discussionmentioning
confidence: 99%
“…103 Thus, the painful syndromes may depend on neuropathy secondary to disturbed homeostasis in the nerves and surrounding tissues. 98 Even if the extraintestinal manifestations are not primarily explained by genetic influences, there is evidence of a genetic component in the associations between IBS and extraintestinal symptoms. 67 The associations between IBS and extraintestinal manifestations in twins may depend on both genetic and environmental conditions.…”
Section: Extraintestinal Manifestationsmentioning
confidence: 99%
“…Several animal models have shown that high intake of fat and/or sugar has led to hyperglycemia, insulin resistance, metabolic disturbances, and histopathological changes with nerve super excitability. 98 Recently, poor dietary habits have been described in IBS patients in several countries. 65,99101 Vitamins and minerals act as cofactors in multiple processes in the cells.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation